“Clerks of Revolution”: Jewish Youth of Province in Events of Civil War (Tambov Province) - V. B. Bezgin; K. A. Yakimov (Научный диалог)
Based on archival materials and published sources, the article deals with the problem of the participation of provincial Jewish youth in the suppression of the insurgent movement on the territory of the Tambov province. The relevance of the study is due to the need to specificate and clarify the historical role of the Jewish youth of the Russian province in the tragic events of the Civil War. The scientific novelty of the work lies in the fact that on the basis of the biographies of the Jews of the “revolutionary turning point” generation, the mechanism of their social lifts is established. For the first time, the role and motives of the participation of Tambov Jewish communists in the fight against the peasant uprising of 1920—1921 under the leadership of A. S. Antonova are studied. The causes of anti-Semitic sentiments in the provincial society of the period of the civil war are revealed. The authors come to the conclusion that the anti-Semitism of urban and rural residents was largely due to the abuse of power by local Jews. It is noted that due to the noticeable penetration of the Jewish element into the Communist Party, in the public consciousness of the peasantry, the Bolsheviks were often identified with the Jews, stimulating the growth of dissatisfaction with the Soviet government within the peasant society.